Pengaruh Media Pembelajaran Berbasis QR Code terhadap Kemampuan Menulis Naskah Drama Siswa Kelas VIII SMP Negeri 14 Kota Jambi - Rachmahtika, Rachmahtika; Kamarudin, Kamarudin; Budiyono, Herman; Purba, Andiopenta; Akhyaruddin, Akhyaruddin (Universitas Batanghari Jambi, 2023)
This research aims to determine the effect of QR Code media on the ability to write drama scripts. This research is a quantitative type of research with a Nonequivalent Control Group pretest and posttest design. The population in this study were all students in class VIII of SMP Negeri 14 Jambi City. Sampling in this study used the Purposive Sampling technique, the sample used was 62 students who were divided into two classes, namely 31 students in class VIII C as the control class and 31 students in VIII E as the experimental class. Research data was obtained through interviews, documentation, and test instruments (Pretest and Posttest). The results showed that the average posttest score for the experimental class was 70.8 and the control class was 64.3. The results of the hypothesis test using the t test, show that the output results obtained a sig value. (2-tailed) is 0.018 < 0.05, so Ha is accepted and Ho is rejected, so there is a significant influence of QR Code media on students' ability to write drama scripts.